Organizational Citizenship Behavior in the Construction of Islamic Boarding School: A Structural Model - Fitriani, Lili Karmela; Wulandari, Linda (Management Department, Universitas Islam Negeri Alauddin Makassar, Indonesia, 2021)
Problems of organizational citizenship behavior among academics, especially teachers in Islamic Boarding Schools, are underrepresented in previous studies. This research was conducted at Islamic Boarding Schools in Kuningan in the context of organizational quality. This study aims to determine the influence of Employee Engagement and Job satisfaction on Organization Citizenship Behavior through Job Organization commitment as an intervening variable. This study includes a type of comparative causal research with a quantitative approach using questionnaires to 130 respondents. The result shows that Employee Engagement and Job satisfaction have a significant effect on Organization Commitment. Employee Engagement, Job Satisfaction, and Organization Commitment have a significant effect on Organizational Citizenship Behavior.